Quality control of solar shortwave and terrestrial longwave radiation for surface radiation measurements at two sites in Cyprus. (October 2016) - Pashiardis, S.; Kalogirou, S.A.
Abstract: Routine measurements of irradiance are valuable for many research fields such as energy applications. However, ground data of solar global radiation can present questionable values. In this study, a set of check procedures is used to test the quality of shortwave and longwave radiation measurements taken at two actinometric stations in Cyprus (Athalassa-inland location and Larnaca-coastal location), during the period November 2012–July 2014. The testing procedures include physically possible limits for all the radiation components and comparisons between global radiation and the sum of direct and diffuse radiation. The quality process is implemented to both the 10-min averaged irradiances, hourly irradiation and the respective daily values. This paper reviews the currently available procedures for quality assessment of the solar shortwave and longwave irradiation data. In the present study, the first level of test includes physical possible limits which are determined by the Daylight Research Group and the Baseline Surface Radiation Network of the World Meteorological Organisation (WMO). The second level of test is a semi-automated procedure that is based on the creation of an envelope in the clearness index and the diffuse to global irradiance ratio. The third level of test is based on the comparison of various radiation parameters including comparison of measured extreme values with theoretical estimations from clear sky-models. The fourth level of test of the quality control procedure refers to the analysis of daily and annual variations of the radiation parameters. Highlights: Procedures used to test the quality of shortwave and longwave radiation measurements. The quality process for the 10 min average irradiances, hourly irradiation and the respective daily values. This paper reviews presently available procedures for quality assessment of the solar irradiation data. The final step of the quality control procedure refers to the analysis of daily and annual variations of radiation parameters.